Surgical Outcome of Hypospadias Repair at KIST Medical College Teaching Hospital - Karki, Kushal; Bhusal, Narayan (Journal of Society of Surgeons of Nepal, 2025)
Introduction: Hypospadias is a common congenital anomaly in male newborns, characterized by an ectopic urethral meatus located on the ventral aspect of the penis. This study aimed to evaluate the surgical outcomes of hypospadias repair performed at KIST Medical College Teaching Hospital over a seven-year period. Methods: We retrospectively reviewed 54 cases of hypospadias repair conducted between January 2016 and January 2023. Patients were followed up in the outpatient department to identify postoperative complications. A total of 47 patients met the inclusion criteria: age under 10 years at the time of surgery and a minimum of one year of postoperative follow-up. Data were collected through telephone interviews with parents and clinical examinations. Surgical outcomes were assessed based on meatal position, skin condition, presence of urethrocutaneous fistula, residual chordee, cosmetic appearance, and urinary stream. Results: The mean age at surgery was 4.34 ± 3.87 years, with a mean follow-up duration of 43.3 months. Surgical techniques included Tubularized Incised Plate (TIP) urethroplasty (68.08%), Bracka’s staged repair (21.27%), STAG repair (6.38%), and meatal advancement procedures (4.25%). A total of 31 complications were observed, with meatal stenosis, urinary stream deviation, and urethrocutaneous fistula being the most frequent. TIP repairs demonstrated the highest incidence of meatal stenosis, whereas Bracka’s repair was associated with multiple complications including residual curvature and fistula formation. The overall surgical success rate was 72%. Conclusion: The outcomes of hypospadias repair are significantly influenced by the location of the urethral meatus and the quality of surrounding tissues. Proximal hypospadias remains surgically challenging and is associated with a higher complication rate. Ongoing postoperative follow-up and refinement of surgical techniques are essential for optimizing both functional and cosmetic outcomes. Long-term, patient-centered evaluation is recommended to assess satisfaction and quality of life.